PERANCANGAN E-COMMERCE PANGAN BERBASIS B2C (STUDI KASUS : KELOMPOK TANI MEKAR MULYA) - Akbar, Nova Nauval; Suhendri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The rapid growth of digital technology has significantly transformed agricultural marketing systems. Mekar Mulya Farmers Group, located in Argalingga Village, Majalengka Regency, faces several challenges in distributing agricultural products, such as long distribution chains, limited market access, and low profit margins due to conventional sales methods. This study aims to design and implement a Business-to-Consumer (B2C) e-commerce platform that directly connects farmers with end consumers. The research adopts the System Development Life Cycle (SDLC) with a waterfall model, which consists of analysis, design, coding, testing, implementation, and maintenance stages. The system was developed using PHP with the CodeIgniter framework, MySQL as the database, and tested with the Blackbox Testing method to ensure functional suitability. The results show that the developed e-commerce platform provides essential features such as product catalogs, order management, payment confirmation, and price transparency, which help build consumer trust. The implementation demonstrates that the system effectively increases farmers’ profit margins, broadens market reach, and streamlines transaction processes. In conclusion, the application of a B2C e-commerce platform in Mekar Mulya Farmers Group proves to be an effective solution for improving operational efficiency, strengthening food security, and supporting farmers’ welfare in the digital era.